Sox10—A Marker for Not Only Schwannian and Melanocytic Neoplasms But Also Myoepithelial Cell Tumors of Soft Tissue. (June 2015) - Miettinen, Markku; McCue, Peter A.; Sarlomo-Rikala, Maarit; Biernat, Wojciech; Czapiewski, Piotr; Kopczynski, Janusz; Thompson, Lester D.; Lasota, Jerzy; Wang, Zengfeng; Fetsch, John F.
<x xml:space="preserve">Abstract</x> Sox10 transcription factor is expressed in schwannian and melanocytic lineages and is important in their development and can be used as a marker for corresponding tumors. In addition, it has been reported in subsets of myoepithelial/basal cell epithelial neoplasms, but its expression remains incompletely characterized. In this study, we examined Sox10 expression in 5134 human neoplasms spanning a wide spectrum of neuroectodermal, mesenchymal, lymphoid, and epithelial tumors. A new rabbit monoclonal antibody (clone EP268) and Leica Bond Max automation were used on multitumor block libraries containing 30 to 70 cases per slide. Sox10 was consistently expressed in benign Schwann cell tumors of soft tissue and the gastrointestinal tract and in metastatic melanoma and was variably present in malignant peripheral nerve sheath tumors. In contrast, Sox10 was absent in many potential mimics of nerve sheath tumors such as cellular neurothekeoma, meningioma, gastrointestinal stromal tumors, perivascular epithelioid cell tumor and a variety of fibroblastic-myofibroblastic tumors. Sox10 was virtually absent in mesenchymal tumors but occasionally seen in alveolar rhabdomyosarcoma. In epithelial tumors of soft tissue, Sox10 was expressed only in myoepitheliomas, although often absent in malignant variants. Carcinomas, other than basal cell–type breast cancers, were only rarely positive but included 6% of squamous carcinomas of head and neck and 7% of pulmonary small cell carcinomas. Furthermore, Sox10 was often focally expressed in embryonal carcinoma reflecting a primitive Sox10-positive phenotype or neuroectodermal differentiation. Expression of Sox10 in entrapped non-neoplastic Schwann cells or melanocytes in various neoplasms has to be considered in diagnosing Sox10-positive tumors. The Sox10 antibody belongs in a modern immunohistochemical panel for the diagnosis of soft tissue and epithelial tumors.